Separation of the bioclimatic spaces of Himalayan tree rhododendron species predicted by ensemble suitability models - Ranjitkar S; Kindt, Roeland; Sujakhu NM; Hart R; Guo W; Yang X; Shrestha, Krishna K.; Xu, Jianchu; Luedeling, Eike (Elsevier, 2014)
The tree rhododendrons include the most widely distributed Himalayan Rhododendron species belonging to the subsection Arborea. Distributions of two members of this sub-species were modelled using bioclimatic data for current conditions (1950–2000). A subset of the least correlated bioclimatic variables was used for ecological niche modelling (ENM). We used an ENM ensemble method in the BiodiversityR R-package to map the suitable climatic space for tree rhododendrons based on 217 point location records. Ensemble bioclimatic models for tree rhododendrons had high predictive power with bioclimatic variables, which also separated the climatic spaces for the two species. Tree rhododendrons were found occurring in a wide range of climate and the distributional limits were associated with isothermality, temperature ranges, temperature of the wettest quarter, and precipitation of the warmest quarter of the year. The most suitable climatic space for tree rhododendrons was predicted to be in western Yunnan, China, with suitability declining towards the west and east. Its occurrence in a wide range of climatic settings with highly dissected habitats speaks to the adaptive capacity of the species, which might open up future options for their conservation planning in regions where they are listed as threatened.